Depression and anxiety among patients with somatoform disorders, panic disorder, and other depressive/anxiety disorders in Taiwan. (30th July 2016) - Huang, Wei-Lieh; Chen, Tzu-Ting; Chen, I-Ming; Ma, Huei-Mei; Lee, Ming-Tzu; Liao, Shih-Cheng; Gau, Shur-Fen
Abstract: The aim of this study is to compare the severity of depression and anxiety in individuals with somatoform disorders, panic disorder, other depressive/anxiety disorders, and healthy controls in a Han Chinese population. According to the DSM-IV-TR-based diagnostic interviews, we recruited 152 subjects with somatoform disorders (SG), 56 with panic disorder (PG), 85 with other depressive/anxiety disorders (OG), and 179 without any psychiatric disorder (NG). The four groups reported on the Beck Depression Inventory-II (BDI-II) and Beck Anxiety Inventory (BAI) for depressive and anxiety symptoms, respectively. Correlation analysis and multivariate regression analysis were used to determine the effects of demographic factors and psychiatric diagnoses on depressive and anxiety symptoms separately. BDI-II scores were not significantly different in SG, PG, and OG but were higher than NG. SG and PG had the highest BAI scores, whereas NG had the lowest. Multiple linear regression analyses revealed that the associated factors for BDI-II were gender, residential location, somatoform disorders, panic disorder, major depressive disorder (MDD), and generalized anxiety disorder, whereas BAI was significantly associated with somatoform disorders, panic disorder, and MDD. Our results strongly suggest the inclusion of clinical assessment of depressive and anxious symptoms in patients with somatoform disorders. Highlights: Somatoform patients have high levels of depression and anxiety. Somatoform comorbidity increases anxiety in major depressive and generalized anxiety disorders. Depression and anxiety are both related with major depressive, panic, and somatoform disorders.